Evaluasi Performance Ban Micheline dan Brigstone Alat Angkut pada Pengangkutan Overburden dari Front Kerja Ke Disposal PT.Kaltim Diamond Coal Kabupaten Berau Kalimantan Timur - Yoga Achmad Rynaldy; Harjuni Hasan; Tommy Trides (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Dump truck tires are an important component in the operation of wheel-type units that require routine inspection because they directly affect the availability and performance of the transport equipment. In the OHT 777 type unit, six tires are used with a configuration of two tires in the front and four tires in the rear. This study aims to evaluate tire performance through the analysis of Key Performance Indicator (KPI) parameters, namely Ton Kilometer Per Hour (TKPH), Tread Utilization Rate (TUR), and tire life (lifetime), in order to assess the achievement of performance targets. The research method uses a quantitative approach with actual data collection in the field, including the preparation stages, primary and secondary data collection, data processing, and preparation of the final report. The data is processed to obtain the tire KPI value. The results of the analysis show that the TUR value for MICHELIN brand tires is 68.9% and BRIDGESTONE is 70.7%, still below the company's target of 85%. The TKPH value for the OHT 773 unit is 149 (with a TKPH rating of 207) and the 777 unit is 241 (with a TKPH rating of 514). The actual lifetime of BRIDGESTONE tires was recorded at 1,698.6 hm and MICHELIN at 2,268 hm, far below the target of 8,500 hm. Tire damage found included impact (23%), sidewall damage (18%), run flat (18%), bread damage (18%), sounder cut (14%), and foreign object puncture (9%). This evaluation is expected to be the basis for improving tire management, so that tire performance in the future can be more optimal and support the smooth operation of the unit.